For the sake of all beings - Kung, Chin. (Taiwan, 2014)
FOREWORD Rare it is to be born as a human. Rare it is to be born when the Buddhadharma is known. Rare to have a wise Master to teach. Rare to have the good fortune to learn from the Master. For over sixty years Venerable Master Chin Kung has been learning the Buddhadharma. For over fifty, with skillful means, great patience, and profound clarity-and the sincere wish that all beings awaken and find true happiness-Venerable Master Chin Kung has tirelessly taught all who wished to learn. Countless gems of wisdom exist throughout all his talks, writing, and correspondence. The book that you are holding holds just a taste of them. A taste of the Buddhadharma for you to savor. For us, his students, it was a privilege and an absolute joy to work on this book. Translations were carefully read and one excerpt after another seemed to step out of the files and into the book. The reading could have gone on much longer, from every translation that we have worked on since the early 1990s.Unfortunately further reading would have meant delaying the printing of this book. That could not be allowed to happen. And so, you now hold this first edition of excerpts from the ongoing work of Venerable Master Chin Kung. Like working on this book, even titling the book was a pleasure. Upon asking some friends for thoughts on what to name the book, one replied," What would sum up Venerable Master Chin Kung's teachings?" The answer immediately came to mind: for the sake of all beings. A file search quickly revealed that Teacher had indeed said that in one of the lectures. ...... Contents Venerable Master Chin Kung Foreword Pure Land Buddha-name Chanting Sutra Recitation Principles Cultivation Three Learnings Three Refuges Five Precepts Six Paramitas AmitabhaVillage Interfaith Harmony and Multiculturalism Education Sources Index
Includes index.
Keywords: Pure Land Buddhism -- Doctrines; Buddhism -- Doctrines